The jigsaw man - Britton, Paul, 1946- (London : Bantam, 1997)
Britton is one of the country's leading criminal psychologists and offender profilers. Dubbed 'the real-life Cracker', he has assisted the police in over 100 cases including the murders of Jamie Bulger and Rachel Nickell.
Keywords: Britton, Paul, -- 1946-; Britton, Paul, -- 1946-; Criminal psychology; Police psychologists -- Great Britain -- Biography; Forensic psychiatry; Case Reports; Case studies